¿Qué significa para un yo ser puesto? Análisis de los capítulos 1 y 2 de la Primera Parte de La enfermedad mortal de Kierkegaard - Rodríguez, Pablo Uriel (Pontificia Universidad Católica del Perú, 2025)
“What is a human being?” and “What is the self?” With this questions, Anti-Climacus–the famous pseudonym of Kierkegaad– begins The Sickness unto Death (1849). The answer follows promptly. A human self is a relationship that relates to itself. This self-relationship has been posited by an other (Andet) or a power (Magt). By relating to itself, this self-relationship thereby relates to this other or power. This paper aims to clarify what it means for the self to be a derived self-relation. To achieve this goal, it analyzes the first two chapters of Anti-Climacus’ book. This analysis is grounded in Kiekegaard’s reflections on the interplay between human freedom and divine omnipotence.

“¿Qué es el ser humano?” y “¿Qué es el yo?”. Con estas preguntas, Anti-Climacus, el famoso pseudónimo de Kierkegaard, inicia La enfermedad mortal (1849). La respuesta no se hace esperar. El yo humano es una relación que se relaciona consigo misma. Esta auto-relación ha sido puesta por un otro (Andet) o un poder (Magt) y al relacionarse consigo misma se relaciona con este otro o este poder. Este artículo intenta clarificar qué significa para el yo ser una auto-relación derivada. Para alcanzar este objetivo, se propone analizar los dos primeros capítulos del libro de Anti-Climacus. Este análisis se basa en las reflexiones de Kierkegaard en torno a la interacción entre la libertad humana y la omnipotencia divina.
What does it mean for a self to be posited? An analysis of Chapters 1 and 2 of the First Part of Kierkegaard’s The Sickness unto Death
Keywords: Kierkegaard; Self; Freedom; Posited-by-another; Omnipotence; Kierkegaard; Yo; Libertad; Puesto-por-otro; Omnipotencia; https://purl.org/pe-repo/ocde/ford#6.03.01